Augustin hérésiologue dans le Contra Iulianum - Ribreau, Mickaël (Revue d'études augustiniennes et patristiques, 2009)
This article analyses the Contra Iulianum to defi ne Augustine’s specific approach of heresy and orthodoxy. Taking up the traditional methods of heresiology, he nonetheless offers new perspectives, as he notably refuses to demonize the heretics and chooses to insist on their inconsistency or their pride. Augustine chiefly elaborates on two arguments that had been seldom used by the previous Fathers, namely the patristic and the liturgical arguments, both of them depending on divine inspiration. The concept of grace is a useful key to understand Augustine’s conception of heresy and his attitude towards the heretics: as a free gift from God, grace allows for the conversion of heretics. While heresy is reprehensible, the heretics can be cured and they can return to the Church they had left.